Reorganizing irrigation: local level management in the Punjab (Pakistan). - Merrey, Douglas J. (1986)
Reprinted with permission from Desertification and Development: Dryland Ecology in Social Perspective, edited by H. Mann and B. Spooner, London, Academic Press, 1982.